Simulation of the Workspace and Manipulability of An Industrial Robot For Research in Robotic Milling Needs - Kijovský Ján; Križan Peter; Hanko Lukáš; Svátek Michal; Bábics Jozef (Journal of Mechanical Engineering)
The paper presents a findings in simulation of the workspace and manipulability of a robotic arm with a spindle. Workspace and manipulability simulation is an important step in next implementation into production cell and it can easily improve CAD and layout design of the production line. Authors would like to present also the torques calculation of individual axes of robotic arms. Presented activities are essential condition for the upcoming experimental design which will be executed in our institute. Goals of research activities on our institute is to determine the functional dependencies between technological parameters of robotic milling, and rigidity of robotic arm, which can be easily evaluated by final machined surface quality and precision of machined components. The paper covers mechanical and simulation system of the existing stand which includes the ABB IRB 1100/0.58 robotic arm.